2016
DOI: 10.1111/jce.12893
|View full text |Cite
|
Sign up to set email alerts
|

Circuit Impedance Could Be a Crucial Factor Influencing Radiofrequency Ablation Efficacy and Safety: A Myocardial Phantom Study of the Problem and Its Correction

Abstract: The lesion and overheated dimensions were significantly larger with lower circuit impedance during irrigated RF ablation and the lesion size was smaller in high impedance ablations. Power delivery adjusted to impedance using a simple equation improved the consistency of lesion formation and prevented overheating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 44 publications
2
36
0
Order By: Relevance
“…For instance, the endocardial contact force was set up to 300 gr and the endocardial force at 30 gr and endocardial impedance close to ideal 120 Ω. 26 Therefore, we might postulate that the lower impedance, employed in our previous experiments, as well as the difference in tip temperature, could explain the different outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, the endocardial contact force was set up to 300 gr and the endocardial force at 30 gr and endocardial impedance close to ideal 120 Ω. 26 Therefore, we might postulate that the lower impedance, employed in our previous experiments, as well as the difference in tip temperature, could explain the different outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…The details of RFA applications in the baseline state ("high baseline impedance") are shown in Table 2. The number applications applied to putative arrhythmia sites was 10.43 ± 3.14 (11,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). There were more applications in patients with scar-related VT compared to patients with idiopathic VPCs (11.92 ± 2.1 [12,[7][8][9][10][11][12][13][14][15] (14,.…”
Section: Ablation Characteristicsmentioning
confidence: 99%
“…Therefore, when ablation is performed in a power-controlled mode, resistance has a direct and negative relationship to current; ablation at lower resistance yields higher current output (and tissue temperature) compared to ablation at a similar power but, higher resistance. 5,8 The relationship of power, current and resistance to lesion dimensions is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study evaluating total circuit impedance demonstrated larger lesion size and a larger zone of heating when the total circuit impedance was lower . In that study, the investigators used a phantom model and altered the surface area of the grounding patch electrode in contact with a conductive fluid to alter the electrical impedance of the entire circuit, including tissue and surrounding environmental impedance.…”
Section: Introductionmentioning
confidence: 99%
“…A prior study evaluating total circuit impedance demonstrated larger lesion size and a larger zone of heating when the total circuit impedance was lower. 6 In that study, the investigators used a phantom model and altered the surface area of the grounding patch electrode in contact with a conductive fluid to alter the electrical impedance of the entire circuit, including tissue and surrounding environmental impedance. We hypothesize that isolated alteration of the surrounding environmental impedance with unchanged tissue impedance in the circuit will preferentially shunt RF electrical current to targeted tissue, and thus affect lesion characteristics.…”
Section: Introductionmentioning
confidence: 99%